2019
DOI: 10.1108/jaee-12-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of GRI-based sustainability reporting: evidence from an emerging economy

Abstract: Purpose The purpose of this paper is to investigate the extent and determinants of sustainability performance disclosures reported by publicly traded companies in Kazakhstan by using the Global Reporting Initiative (GRI) framework. Among the different possible determinants, stand-alone sustainability reporting (SR), reporting language, leverage, cash flow capacity, profitability, size, age and auditor type were selected to investigate their impacts on the quality and scope of sustainability information. Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
2
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(168 citation statements)
references
References 118 publications
11
124
2
31
Order By: Relevance
“…The average word count in sustainability reporting has been showing an increasing trend from the year 2012 (2264 words) to 2015 (3039 words) in Sri Lanka (Dissanayake et al, 2019). Orazalin and Mahmood (2019) found that standalone reporting, reporting language, profitability, size, and auditor type influenced the nature, extent, and quality of sustainability reporting among Kazakhstani companies for the years of 2013-2015.…”
Section: Literature Reviewmentioning
confidence: 90%
“…The average word count in sustainability reporting has been showing an increasing trend from the year 2012 (2264 words) to 2015 (3039 words) in Sri Lanka (Dissanayake et al, 2019). Orazalin and Mahmood (2019) found that standalone reporting, reporting language, profitability, size, and auditor type influenced the nature, extent, and quality of sustainability reporting among Kazakhstani companies for the years of 2013-2015.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Las teorías de legitimidad e institucional, son las más usadas para explicar las motivaciones de las organizaciones para el reporte ambiental y de sostenibilidad, (Cormier et al, 2005;Orazalin Análisis de información y factores de desempeño ambiental y de economía circular en empresas peruanas Analysis of information and factors of environmental performance and circular economy in Peruvian companies y Mahmood, 2019). Esta preocupación de las empresas por comunicarse de manera efectiva con las partes interesadas, mejorar la reputación corporativa y justificar su legitimidad en la sociedad sobre su desempeño de sostenibilidad de forma más amplia es una de las causas de la vasta difusión de los reportes de sostenibilidad en el mundo (Alonso-Almeida et al, 2015;Landrum y Ohsowski, 2018;Marimon et al, 2012;Orazalin y Mahmood, 2019).…”
Section: Teorías Sobre Reporte Medioambientalunclassified
“…Aparte de ello, algunos estudios de organizaciones de economías emergentes, señalan que la influencia institucional en el reporte de sostenibilidad ha sido relevante por parte de organizaciones no gubernamentales internacionales como las Naciones Unidas o Global Reporting Initiative, en mayor medida que los entes reguladores gubernamentales. No obstante, este reporte voluntario, en algunos casos, no ha resultado ser una herramienta efectiva para conocer todas las necesidades de las empresas y las de sus grupos de interés en sus desempeños de sostenibilidad (Ali y Frynas, 2018;Alonso-Almeida et al, 2015;Moneva et al, 2019;Orazalin y Mahmood, 2019).…”
Section: Introductionunclassified
“…Social sustainability is the promotion of social justice through equitable resource allocation, poverty alleviation, and adequate access to social services (such as education, nutrition, health, etc.). Environmental sustainability involves the conservation of biodiversity, attaining atmospheric balance, and responsible utilization of natural capital (Brammer and Pavelin 2008;Orazalin and Mahmood 2020). Economic sustainability occurs when social and environmentally sustainable development is financially feasible.…”
Section: Fox Et Al's Csr Policy Framework Was Proposed Bymentioning
confidence: 99%
“…Using the standards of the Global Reporting Initiative (GRI) framework, Orazalin and Mahmood (2020) investigated the determinants of sustainability performance disclosures of publicly traded firms in Kazakhstan. Data for the study was collected from the Kazakhstan Stock Exchange between 2013 and 2015.…”
Section: Selected Studies Of Csr In Kazakhstanmentioning
confidence: 99%